Isavuconazole as an optimal treatment option for multiple pathogens induced severe pneumonia in immunocompromised hosts: a case series report - Wang, Xinyin; You, Yanjing; Chen, Shuyang; Wang, Peiyu; Zeng, Shengyuan; Zhuang, Liying; Wang, Meng; Lai, Guoxiang; Yu, Zongyang; Yu, Guoqing; Wen, Wen (Frontiers in Medicine, 2025)
BackgroundTreating severe pneumonia caused by multiple pathogens in immunocompromised hosts (ICHs) presents significant challenges. Isavuconazole (ISA), a next-generation triazole antifungal agent, has shown promise in managing fungal infections. However, clinical evidence regarding its efficacy in cases of complex infections involving multiple pathogens in ICHs remains limited.Case presentationThis study describes a case series of three ICHs diagnosed with severe pneumonia, including invasive aspergillosis (IA). All three patients received ISA-based personalized antimicrobial regimens. Alleviation of symptoms was observed in all patients following antimicrobial treatment, with notable absorption of pulmonary lesions and no significant hepatorenal toxic side effects, with no recurrence observed.ConclusionICHs are highly susceptible to fungal infections, and the severity of their condition can escalate dramatically, with a significant risk of mortality, when severe pneumonia caused by multiple pathogens occurs concurrently. A stepwise treatment strategy, which balances the use between immunosuppressant and effective antimicrobial treatment, is crucial. The selection of appropriate drugs should account for potential adverse drug reactions (ADRs). In this case series, ISA exhibited robust efficacy in treating IA with minimal ADRs. Therefore, ISA represents a valuable option for managing severe pneumonia in ICHs, particularly in the context of IA and co-infections caused by multiple pathogens.